Essentials of digital signal processing using Matlab - Ingle, Vinay K.; Proakis, John G. (PWS BookWare companion series, 2012)
Uses MATLAB[registered] as a computing tool to explore traditional DSP topics and solve problems to gain insight. In this title, practical examples are discussed and useful problems are explored